Tree-ring Dating of the Little Ice Age Maxima of Arolla Glaciers (Valais, Switzerland) - Melaine Le Roy; Kurt Nicolussi; Christian Schlüchter (Revue de Géographie Alpine)
Little Ice Age (LIA) glacier variations are well constrained in the Alps, partly thanks to an unparalleled body of historical sources. When absent, tree-ring dating can be used to obtain accurate chronological information on glacier maxima. To do so, it is necessary to focus on the trees that immediately bordered the former maximum extent reached by the glaciers in historical times. Here, we present tree-ring dating results for newly sampled wood material and archival data from the forefields of two glaciers in the Pennine Alps, Tsijiore Nouve and Glacier d’Arolla. These sites have historical sources dating back to the early 19th century, i.e. slightly more recent than for the best known Alpine glaciers. At Tsijiore Nouve, the dating of trees embedded in the LIA outer moraine at the valley bottom and of bordering living trees both indicate the presence of the ice near this location as early as summer 1813 CE and of a maximum extent reached in 1816 CE. This is highly consistent with available historical sources pointing to a LIA maximum in 1817 CE. At Glacier d’Arolla we dated the outermost moraine to winter 1816/1817 CE, which is synchronous, despite different glacier response times. The dates we obtained are significantly earlier than available evidence at other Alpine glaciers during the same advance. Our results highlight the ability of tree-ring dating to derive accurate calendar dates for glacier maxima and show – for the first time in the Alps - that some glaciers were already at or near their LIA maxima when the cooling associated with the Mount Tambora volcanic eruption occurred.